TRANSLATION OF FIQH AL-SIRAH AL-BOUTI: ANALYSIS OF SELECTION OF WORDS AND SENTENCE STRUCTURES - Saifulah bin Samsudin; Khairatul Akmar bin Abdul Latif; Salman bin Zainal Abidin; Ahmad Redzaudin Ghazali (Journal of Islamic, Social, Economics and Development, 2017)
: One of the disciplines of Islamic studies that became the focus of the Arabic-Malaytranslators is Sirah's discipline. However translation is not an easy process. It requirestranslators to master the field and master the source language and target language. Thesource style of the source text author also affects the translation process. Hence, this studyfocuses on the accuracy of the translation contained in the Fiqh Sirah translation of SheikhMuhammad Said Ramadan al-Boutiy by Ustaz Darus Sanawi. The main objective of the studyis to elaborate the translation method used by the translator by emphasizing the aspects ofvocabulary and sentence structure. The research data was taken from Fiqh al-Sirah'stranslation book by Ustaz Darus Sanawi's translation of the Dewan Fajar Bakti 1983.Findings show that both aspects are influenced by the highly visible Direct Translationapproach.